Meningkatkan Kapasitas Terminal dan Kepuasan Penumpang Bandara Hang Nadim Batam Menggunakan Regresi Linear Sederhana dan Customer Satisfaction Index (CSI) - Eliska Theodora Elizabeth; Andri Irfan Rifai; Mulia Pamadi (Jurnal Manajemen Teknologi & Teknik Sipil, 2022)
Evaluation and analysis of terminal capacity and user satisfaction is one of the things that needs to be done to prepare for all post-COVID-19 conditions. Airport passenger satisfaction is an important component in airport service management because it affects the demand for travel accessand airport revenue. The purpose of this study is to evaluate capacity and analyze passenger satisfaction at Hang Nadim airport in Batam post-COVID-19. The method used is Simple Linear Regression and Customer Satisfaction Index (CSI). Sampling was done by probability sampling with the population of Hang Nadim airport passengers. The data collected in the form of data on the number of passengers departing during 2012 to 2021. Direct observations were carried out by distributing questionnaires to 50 respondents. With the linear regression method, passenger flows will be obtained until the post-covid-19 pandemic, so that a capacity evaluation will be carried out at the airport. Based on the results of the evaluation and analysis carried out, it was found that the estimated number of passengers after the COVID-19 pandemic in In 2022 the predicted number of arriving passengers is 1,553,669 and in 2023 as many as 1,444,876 people.. There is one facility that needs to be improved, namely the arrival hall which was originally 3,452 m² to 4,525 m². While other facilities are still in the category of fulfilling. The level of passenger satisfaction with the quality of Batam's Hang Nadim airport is 53.96 percent, which is quite satisfied according to the Customer Satisfaction Index approach.